2012
DOI: 10.1186/1471-2431-12-82
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence and early child growth: a community-based cohort study in Nicaragua

Abstract: BackgroundThis study analyses whether a mother’s exposure to different forms of Intimate Partner Violence (IPV) during pregnancy was associated with the index child linear growth, and whether these associations were modified by the gender of the child.MethodsA pregnancy cohort of 478 women in León, Nicaragua, resulted in 461 live births. From this group, 81% (375/461) children were available for anthropometric follow-up at 40 to 46 months. Analysis of covariance (ANCOVA) was used to assess the association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
2
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 30 publications
0
39
2
6
Order By: Relevance
“…Another study revealed that adjusting for demographics reduced the strength of association for undernutrition but remained marked for wasting and stunting ). Yet another study found that after adjusting for maternal age, marital status, parity, residency and social economic status, stunting was still significant (Salazar et al, 2012). These findings insinuate that IPV alone has an impact on child's undernutrition, wasting and stunting and that maternal demographic factors may contribute to the severity of the child growth failures.…”
Section: Maternal Characteristics Associated With Growth Failuresmentioning
confidence: 92%
See 4 more Smart Citations
“…Another study revealed that adjusting for demographics reduced the strength of association for undernutrition but remained marked for wasting and stunting ). Yet another study found that after adjusting for maternal age, marital status, parity, residency and social economic status, stunting was still significant (Salazar et al, 2012). These findings insinuate that IPV alone has an impact on child's undernutrition, wasting and stunting and that maternal demographic factors may contribute to the severity of the child growth failures.…”
Section: Maternal Characteristics Associated With Growth Failuresmentioning
confidence: 92%
“…Higher education and decision-making among mothers were associated with higher WHZ, HAZ, and WAZ scores implying that these children were growing normally or tended towards obesity . A number of studies found low maternal education level associated with low Z-scores Salazar et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations